LARANGAN MENIKAH SATU KAUM DALAM MASYARAKAT SUKU PEKAL DITINJAU DARI PERSPEKTIF ISLAM (STUDI KASUS DI KECAMATAN MALIN DEMAN KABUPATEN MUKOMUKO) - Devi Marlina (Sekolah Pasca Sarjana IAIN Bengkulu, 2017)
The purpose of this study is to know and analyze the marriage of one kaum in Pekal society in Malin Deman sub-district of Mukomuko regency in banned and to know the view of Islamic law concerning the prohibition of marriage of one people in Pekal society in Kecamatan Malin Deman of Mukomuko Regency. The results of the study showed that the prohibition of marrying one of the people in Pekal sub-district, Malin Deman sub-district of Mukomuko Regency, due to the relative nature of the kinship relationship, is feared to damage the relationship of silaturrahim, it is feared there will be marriage between siblings, consider one brothers and to decide which dunsanak ) which does not, educate shame, and a strong conviction that there will be a bad thing against the descent and view of Islamic law concerning the prohibition of marriage of one kaum in Pekal tribe society in Malin Deman sub-district Mukomuko regency is not in accordance with Islamic law because one brother not included in those who are forbidden to be married according to the Qur’an and Sunnah. Thus can be said marriage of one punishable people may (mubah).